2000
DOI: 10.1095/biolreprod62.4.959
|View full text |Cite
|
Sign up to set email alerts
|

Human Decidual Natural Killer Cells Express the Receptor for and Respond to the Cytokine Interleukin 151

Abstract: The natural killer (NK) cells that are present in the uterine mucosa (decidua) during early pregnancy have a distinctive phenotype, CD56(bright) CD16(-). These cells have previously been shown to proliferate and be activated by interleukin (IL)-2. However, IL-2 is absent from the decidua and placenta, and we have therefore investigated whether IL-15 is present in the uterus and can act on decidual NK cells. Both IL-15 mRNA and protein were found in a variety of cells but particularly in decidual macrophages. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
155
1
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(187 citation statements)
references
References 56 publications
18
155
1
13
Order By: Relevance
“…Similarly, IFN-γ induces IL-15 mRNA expression in monocytes and NK cells [49,50,51]. The concentrations of IL-15 produced by human islets were low, similar to data obtained in other cell types [49,52]. It has been shown that picomolar amounts of IL-15 are effective in maintaining NK cell survival in serum-free media [49], suggesting that the observed IL-15 production by human islets might be physiologically relevant.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, IFN-γ induces IL-15 mRNA expression in monocytes and NK cells [49,50,51]. The concentrations of IL-15 produced by human islets were low, similar to data obtained in other cell types [49,52]. It has been shown that picomolar amounts of IL-15 are effective in maintaining NK cell survival in serum-free media [49], suggesting that the observed IL-15 production by human islets might be physiologically relevant.…”
Section: Discussionsupporting
confidence: 54%
“…31 It is reasonable to hypothesize that the unique functional properties of dNK cells might be attributed to the particular cytokine milieu in the decidua. 32 In this study, we demonstrated that CD3 2 CD56 bright CD25 1 dNK cells preferentially localize to the maternal/fetal interface in early human pregnancy, and we also found that this cell subset displays a more activated phenotype than CD3 2 CD56 bright CD25 2 dNK cells. Furthermore, coculture of pNK with trophoblasts increased CD25 expression and the frequency of TGF-b-and IL-8-producing pNK cells.…”
Section: Discussionsupporting
confidence: 63%
“…Published data obtained from in situ hybridization studies suggest that macrophages present in the pregnant mouse uterus may be responsible for the production of IL-15 [22], and it has also been shown that macrophages are the major source of IL-12 and IL-18 in most tissues [23,24]. These cytokines were recently shown to be capable of activating NK cells [25,26], and King and co-workers described IL-15 receptor expression on human decidual NK cells [27]. Impaired remodeling of maternal vessels, a hypocellular decidua and decreased development of the metrial gland observed in implantation sites with inhibited recruitment of a4b7 + leukocytes suggest altered uNK cell function, although litter size and birth weight in both b7-integrin -/-and P-selectin -/-mice are comparable to those of untreated or Hermes-1-treated wild-type pregnancies as also reported by Croy et al [20].…”
Section: Discussionmentioning
confidence: 98%